2014
DOI: 10.4321/s1886-36552014000100008
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of prescription warning labels within an underserved population

Abstract: *Objective: To understand how underserved populations attend to prescription warning label (PWL) instructions, examine the importance of PWL instructions to participants and describe the challenges associated with interpreting the information on PWLs. Methods: Adults from an underserved population (racial and ethnic minorities, individuals with low income, older adults) who had a history of prescription medication use and were able to understand English took part in semistructured interviews. Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 21 publications
(41 reference statements)
0
28
1
Order By: Relevance
“…Different from previous studies which focused predominantly on auxiliary labels, [1][2][3]9] this study investigated the patients' attentiveness to warnings and precautions which were presented, along with their particulars and dosing instructions, on the same drug label. The findings confirm that approximately 80% of patients receiving medications from public hospitals in Malaysia did not pay attention to such information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different from previous studies which focused predominantly on auxiliary labels, [1][2][3]9] this study investigated the patients' attentiveness to warnings and precautions which were presented, along with their particulars and dosing instructions, on the same drug label. The findings confirm that approximately 80% of patients receiving medications from public hospitals in Malaysia did not pay attention to such information.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]11] Nonetheless, it is difficult to assess health literacy of all patients during the clinical encounter, especially in a busy health setting. [12] Rather, this study found a positive relationship between polypharmacy and patients' attentiveness to warnings and precautions on labels, with all the possible confounders, including age, ethnicity and employment status, adjusted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptions of consumers ignoring warning labels is consistent with published literature related to Australian consumers 23 and globally. 24,25 To counter this, several studies have tested ways to enhance the noticeability of warning labels through depicting organ specific damage, 26 black-box warnings and the addition of text and colour 13 . One study comparing warning labels used in Australia and France concluded that participants were more readily able to delineate risk levels from the French labelling system due to the inclusion of medication risk categorisation and the effective use of colour and graphics.…”
Section: Discussionmentioning
confidence: 99%
“…When individuals read the drug labels, we can easily find instructions like: 'take on an empty stomach', 'take 1 pill every 12 hours by mouth with a meal', 'do not chew or crush', 'swallow whole', 'take with food, 'avoid prolonged or excessive exposure to direct and/or artificial sunlight while taking this medication' or 'medication should be taken with plenty of water'. A significant percentage of older adults failed to understand these instructions [10,11]. For those who suffer from mild cognitive impairment (MCI), they may find these instructions less understandable.…”
Section: Introductionmentioning
confidence: 99%